Efficiency-based prioritization of stakeholders using data envelopment analysis - Soheil Azizi; Reza Rasinojehdehi (Big Data and Computing Visions)
This paper introduces a novel approach to stakeholder prioritization by employing Data Envelopment Analysis (DEA). The study utilizes five key criteria-stakeholder power, urgency, legitimacy, level of involvement, and project impact-to quantitatively evaluate stakeholder efficiency. DEA models tailored for each stakeholder are applied, yielding a comprehensive prioritization depicted in numerical form. The methodology showcased in this research harnesses the versatility of DEA in stakeholder analysis. The resulting prioritization aids project managers in strategic decision-making, offering valuable insights to enhance project success and minimize negative impacts. This paper contributes a practical and effective tool for project managers seeking to optimize stakeholder engagement and project outcomes.